PRAME expression in 155 cases of metastatic melanoma. (8th November 2020) - Gradecki, Sarah E.; Slingluff, Craig L.; Gru, Alejandro A.
Abstract: Background: PRAME ( pr eferentially expressed a ntigen in me lanoma) is a promising immunohistochemical marker in distinguishing benign from malignant primary cutaneous melanocytic lesions and lymph node deposits. We hypothesize that PRAME may also reliably identify melanoma metastases that are clinically detected in skin, lymph nodes, or small intestine. Methods: A total of 155 cases of metastatic melanoma to lymph node (N = 54) and non‐lymph node (N = 101) sites were stained with an antibody against PRAME. Nuclear expression was scored in tumor cells as negative, 1% to 25% (1+), 26% to 50% (2+), 51% to 75% (3+), or 76% to 100% (4+). Results: PRAME expression was seen in 151/155 (97.4%) cases, with 4+ expression in 64 cases (41.3%), 3+ expression in 46 cases (29.7%), 2+ expression in 18 cases (11.6%), and 1+ expression in 23 cases (14.8%). Lymph node metastases were more likely to show lower expression as compared to metastases to other anatomic sites ( P = 0.003). Conclusions: A high level of PRAME immunoreactivity was identified in this cohort of metastatic melanoma. Lymph node metastases showed more focal or absent PRAME expression as compared to metastases to other sites. Overall, PRAME is a useful tool for confirming the diagnosis of melanoma in a metastatic setting, in both nodal and visceral deposits.